Records and information management : fundamentals of professional practice - Saffady, William (Lanham, Maryland : Rowman & Littlefield, 2021)
This is the "go to" book for newly appointed records managers, as well as experienced records and information management (RIM) professionals who want a review of specific topics. The approach here is practical rather than theoretical and emphasizes best practices and published standards
Preface -- Chapter 1: Records Management as a Business Discipline -- Chapter 2: Preparing Retention Schedules i: Collecting Data -- Chapter 3: Preparing Retention Schedules ii: Making Retention Decisions -- Chapter 4: Managing Paper Records -- Chapter 5: Document Imaging -- Chapter 6: Managing Digital Documents -- Chapter 7: Protecting Essential Records.
Keywords: RECORDS MANAGEMENT